If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8v + 12 = 4v + -6 Reorder the terms: 12 + 8v = 4v + -6 Reorder the terms: 12 + 8v = -6 + 4v Solving 12 + 8v = -6 + 4v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-4v' to each side of the equation. 12 + 8v + -4v = -6 + 4v + -4v Combine like terms: 8v + -4v = 4v 12 + 4v = -6 + 4v + -4v Combine like terms: 4v + -4v = 0 12 + 4v = -6 + 0 12 + 4v = -6 Add '-12' to each side of the equation. 12 + -12 + 4v = -6 + -12 Combine like terms: 12 + -12 = 0 0 + 4v = -6 + -12 4v = -6 + -12 Combine like terms: -6 + -12 = -18 4v = -18 Divide each side by '4'. v = -4.5 Simplifying v = -4.5
| L^2-29L=54 | | 7x-0.5=2.5 | | -64-8g=8 | | -9(x+3)=4-8x | | 80=8x | | 3x-45=57 | | 5a+6-4a=4 | | 7+-d=3 | | 32-8x=-8 | | X^3-2xy^2+x^2y^3=0 | | 3r+12= | | 24-2x=10x | | 2x+(5-x)=3-3x+6 | | 2b+4=-18-4 | | .3+.6m=.6m-.6 | | 4x^2-3x-9=0 | | 52h=130 | | (7f-49)=7 | | 2-6=a-1 | | 3x+4x=6x-1 | | 4x+8=2x+48 | | 9+x=-4-6(6x+4) | | 9abc+10a+4b= | | 2a-4b=6 | | 4x-13=5-3(x-1) | | k+2=8 | | -6y^2-5y+2=0 | | 42=3x+4x | | (k/4)+6=-2 | | (2d-1)=15 | | 36-6e=6 | | 5x-2=1225 |